Knowledge and Association of Solar Pump Users Regarding Vegetable Production Technology in Jaipur Rajasthan - Pramod; Shobhana Gupta, K. C. Sharma, B. S. Badhala; R. N. Sharma (Indian Journal of Extension Education, 2022)
Rajasthan has outstanding solar radiation in India and a solar water pump is a great investment that makes money in the long run. The present study was conducted in Jaipur district with 120 beneficiary and non- beneficiary farmers regarding knowledge about the improved practices of vegetable production possessed by solar pump users during 2020. The practices namely- selection of improved seed variety, time of sowing, seed treatment, organic and chemical manure application of irrigation at the right time, intercultural operations, weed management, insect and disease management etc. were found as popular practices. The results of the study revealed that majority (95%) of beneficiary fall into the category of medium to high level of knowledge against 80 per cent of the non-beneficiary were falling under low to medium knowledge level. It can be summarized that the variables viz., education, occupation, annual family income, size of land holding, farm mechanization, utilization of information, contact with extension agents etc. were found significant with their knowledge of vegetable production technology. The results also depicted that age was found in non-significant relationship with knowledge of vegetable production technology. There was a significant association between knowledge of vegetable production technology of non-beneficiaries with their occupation, size of land holding and contact with extension agents. In case of age no association was found between age and knowledge of vegetable production technology for both the beneficiary and non-beneficiary farmers.